Pengaruh Pemberian Minuman Kombinasi Sari Kurma (Phoenix dactylifera) dan Garam NaCl terhadap Tekanan Darah dan Lama Periode Pemulihan Denyut Nadi pada Atlet Sepak Bola - Efrilia Maulana; Siti Wahyuningsih; Natalia Desy Putriningtyas (Universitas Muhammadiyah Semarang, 2019)
The athlete's achievement is related to the athlete's performance in a match. The performance can be seen in blood pressure and pulse. The administration of carbohydrateelectrolyte drinks influenced blood pressure and pulse. Drinks combination of sari dates and NaCl contain carbohydrates and electrolytes which helps to improve the performanceof athletes by delaying fatigue. This research to determine the effect of combination palm juice extracts and NaCl on blood pressure and the period of recovery of the pulse of a soccer athlete. The quasi-experimental cross over study was completed. This research was carried out in the Wates square. Subjects in this study were Hizbul Wathan Wates Football School(SSB) athletes. The subjects received one experimental used 300 ml combination drink of palm juice and NaCl or control drink, namely sugar water after a washout period of six days. Blood pressure measurements were carried out fifteen minutes before exercise and fifteen minutes after exercise, while pulse measurements were carried out fifteen minutesbefore exercise and five minutes, ten minutes, fifteen minutes after exercise. The statistical test used was Shapiro Wilk, Paired t-test and Independent T-test. The results of statistical analysis showed that there was no significant effect on the combination of dates, and NaCl combined with systole and diastolic blood pressure (p> 0.05), and there was a significant effect on the combination of dates palm juice and NaCl on pulse recovery five minutes, ten minutes and fifteen minutes after exercise (p <0.05). There was no significant effect on the combination of date palm juice and NaCl on blood pressure, and there was a significant effect on the combination of dates and NaCl combination drinks on the recovery of pulsefive minutes, ten minutes and fifteen minutes after exercise. Keywords: Dates, NaCl, Soccer, Blood Pressure, Pulse